ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI WHISTLEBLOWING INTENTION MENGGUNAKAN GRAHAM’S MODEL [WHISTLEBLOWING INTENTION: GRAHAM'S APPROACH MODEL OF PRINCIPLED ORGANIZATIONAL] - Setyorini Setyorini; Donifaizal Donifaizal (Jurnal Penelitian Akuntansi (JPA), 2020)
This research aims to examine the effect of factors that influence the whistleblowing intentions. This research used a graham model which consists of problem seriousness, personal responsibility, and personal costs to propose a theoretical model to explain the intention of accounting employees to do whistleblowing.This research was a quantitative approach. The data used are primary data in the form of questionnaires with the research population was the employees of accounting at several BPR banks in Sleman district. This research uses a convenience sampling technique with 61 respondents. The analytical method used was Structural Equation Modeling (SEM) using Partial Least Square (PLS) to verify the factors that influence the intention to do whistleblowing. Results of this research show that: (1) Perception of the problem seriousness did not affect the whistleblowing intention; it is proved by the significance value 0.505. (2) Perception of personal responsibility has a significant positive effect on whistleblowing intentions, and it is confirmed by the coefficient 0.054 and the significance value 0.003. (3) Perception of personal cost has a significant negative effect on whistleblowing intentions; it is proved by the coefficient value of -0.387 and the significance value of 0.004.Bahasa Indonesia Abstrak: Penelitian ini bertujuan untuk menguji pengaruh faktor-faktor yang mempengaruhi niat whistleblowing. Penelitian ini menggunakan model graham yang terdiri dari masalah keseriusan, tanggung jawab pribadi, dan biaya pribadi untuk mengusulkan model teoritis untuk menjelaskan niat karyawan akuntansi untuk melakukan whistleblowing. Penelitian ini merupakan pendekatan kuantitatif. Data yang digunakan adalah data primer berupa kuesioner dengan populasi penelitian adalah pegawai akuntansi di beberapa bank BPR di Kabupaten Sleman. Penelitian ini menggunakan teknik convenience sampling dengan 61 responden. Metode analisis yang digunakan adalah Structural Equation Modeling (SEM) menggunakan Partial Least Square (PLS) untuk memverifikasi faktor-faktor yang mempengaruhi niat melakukan whistleblowing. Hasil penelitian ini menunjukkan bahwa: (1) Persepsi masalah keseriusan tidak mempengaruhi niat whistleblowing; itu dibuktikan dengan nilai signifikansi 0,505. (2) Persepsi tanggung jawab pribadi memiliki pengaruh positif signifikan terhadap niat whistleblowing, dan itu dikonfirmasi oleh koefisien 0,054 dan nilai signifikansi 0,003. (3) Persepsi biaya pribadi memiliki efek negatif yang signifikan terhadap niat whistleblowing; itu dibuktikan dengan nilai koefisien -0,377 dan nilai signifikansi 0,004.